PENGARUH AKTIVASI KARBON DIOKSIDA PADA PRODUKSI KARBON AKTIF MONOLIT DARI KAYU KARET - Herniyanti, Septa; Taer, Erman; ', Sugianto (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Activated carbon monoliths from rubber wood have successfully been fabricated using combined physical-chemical activation and chemical activation. The process of combination of physical-chemical activation was started from physical activation process by flowing CO2gas for 2 hours at temperature of 800 oC, then applying chemical activation process by immersing the carbon in 3 M KOH solution and 2,5 M H3PO4 solution. The samples activated by the combination of physical-chemical activation were named as A1and those that were activated by chemical activation were named as sample A2. Both activation methods yielded different activated carbon. The physical properties analyzed were density, porosity, and BET surface area, whereas the electrochemical property obtained from measurements using cyclic voltammogram method was specific capacitance. N2adsorption-desorption gas treatment resulted BET surface area of 542.586 m2g-1 and 115.147 m2g -1 for each sample, respectively. The resulted specific capacitances of the measurement using the cyclic voltammogram method for each sample were 43.67 F g-1and 37.74 F g-1 , respectively. Based on all obtained data analysis, it can be concluded that the physical-chemical activation produced larger BET surface area and higher specific capacitance than those resulted from chemical activation for supercapacitor cells.